0544 Reconsidering Stimulus Control: Activities in Bed Associated with Sleep-Related Outcomes. (27th May 2020) - Phan, S; Perlis, M L; Hale, L; Branas, C; Killgore, W D; Wills, C C; Grandner, M A
Abstract: Introduction: The typical advice is that in order to avoid insomnia, people should avoid activities in bed other than sleep. Yet, activities such as reading and watching TV in bed are common. Methods: Data were obtained from the Sleep and Health Activity, Diet, Environment, and Socialization (SHADES) Study, N=1, 007 adults age 22-60. Sleep hygiene was assessed using items from the Sleep Practices and Attitudes Questionnaire (SPAQ), which asked whether respondents agree/disagree that they do the following in bed: Read, Watch TV, Eat, Work, Worry, and/or Argue. These were analyzed in relation to Insomnia Severity Index (ISI) score, Pittsburgh Sleep Quality Index (PSQI) score, Epworth Sleepiness Scale (ESS) score, Fatigue Severity Scale (FSS) score, and self-reported sleep duration (TST), sleep latency (SL), and wake after sleep onset (WASO). Covariates included age, sex, education, and income. Results: Those that frequently engaged in activities were: reading (75%), watching TV (63%), eating (42%), working (32%), worrying (82%), and arguing (23%). Reading was associated with less WASO (B=-14min, p=0.02). Watching TV was associated with higher ISI (B=1.22, p=0.04), PSQI (B=1.04, p=0.007), and ESS (B=0.87, p=0.049), and less TST (B=-0.29, p=0.04). Eating was associated with higher ISI (B=1.75, p=0.01), PSQI (B=1.23, p=0.008), and FSS (B=4.36, p=0.002). Working was associated with higher ISI (B=1.82, p=0.019), PSQI (B=1.65, p=0.001), and ESS (B=1.78, p=0.002). Worrying was associated with higher ISI (B=7.34, p<0.0005), PSQI (B=4.40, p<0.0005), ESS (B=2.53, p=0.001), FSS (B=9.51, p<0.0005), and SL (B=19.39, p<0.0005), and less TST (B=-0.55, p=0.023). Arguing was associated with higher ISI (B=3.78, p<0.0005), PSQI (B=3.15, p<0.0005), ESS (1.47, p=0.023), and SL (B=10.97, p=0.013), and lower TST (B=-0.71, p=0.001). Conclusion: Individuals who perform mentally distressing activities such as worrying and arguing experience especially worse sleep, and those who read in bed have fewer awakenings. Support: The SHADES study was funded by R21ES022931. Dr. Grandner is supported by R01MD011600.